2015
DOI: 10.3126/jucms.v3i4.24267
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathological Evaluation of Thyroid by Fine Needle Aspiration Cytology and Correlation with T3 T4 and TSH Levels

Abstract: INTRODUCTION: Fine Needle Aspiration Cytology (FNAC) of the thyroid gland is now a well-established, first line diagnostic test for the evaluation of thyroid lesions. An FNA is performed along with Thyroid Function Test (TFT) profile to correlate cytology with hormonal function in symptomatic or asymptomatic patients. MATERIALAND METHODS: Total of 117 cases of FNAC of thyroid lesions were selected who had undergone TFT profile. The lesions were evaluated cytologically and categorized according to Bethesd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
2
0
1
Order By: Relevance
“…Our present study showed that thyroid lesions are common in females with female to male ratio 9 : 1 which is similar to the study done by Poudel et al 12 17 , among the non neoplastic lesion colloid goitre was the common thyroid lesion followed by lymphocytic thyroiditis which had the similarity with the present study.…”
Section: Resultssupporting
confidence: 92%
“…Our present study showed that thyroid lesions are common in females with female to male ratio 9 : 1 which is similar to the study done by Poudel et al 12 17 , among the non neoplastic lesion colloid goitre was the common thyroid lesion followed by lymphocytic thyroiditis which had the similarity with the present study.…”
Section: Resultssupporting
confidence: 92%
“…Compared to present study, Poudel et al reported the age of patients in 14 to 70 years range and mean age as 38.8 years. 27 Similar to present study, in their study too, majority of patients (61.5%) were ≤40 years of age. Siddegowda et al on the other hand reported the age range of patients as 11 to 80 years but found most of the cases (56.0%) in age range 21-40 years itself.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study most common affected age group was fifth decade i.e. 41-50, whereas in other studies like Suman et al, [13], Leonard et al, [14], Silverman et al, [15] and Patel et al, [16] most common age group affected ranged from 20-50 years. Nodular goiter as most common nonneoplastic lesion with 33.75% similar to studies done by Sood et al, [18] and Mahar et al, [17] and most common neoplastic lesion as papillary thyroid carcinoma with 18.75% similar to studies done by Mahar et al, [17], Sood et al, [18] and Jayaram et al, [19].…”
Section: Discussioncontrasting
confidence: 56%